2021
DOI: 10.1155/2021/5775040
|View full text |Cite
|
Sign up to set email alerts
|

Yunnan Black Tea Flavonoids Can Improve Cognitive Dysfunction in Septic Mice by Activating SIRT1

Abstract: This study explored the effect and mechanism of Yunnan black tea flavonoids (YBTF) on cognitive dysfunction in septic mice. The mice were induced sepsis, the serum was determined using kits, and the tissue was determined by qPCR assay. The Yunnan black tea flavonoids were checked using HPLC. The test results showed that compared with the model group, YBTF could increase the survival rate of the mice; meanwhile, YBTF could also increase the total distance travelled, number of stands, and number of groomings, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…An overview should be done on related mechanisms in the activation of physiological pathways, such as the SOD (Superoxide dismutase) system, CAT (Catalase), or the downregulation of pro-inflammatory cytokines, such as TNF-α, related to the downstream activation of oxidative stress. Flavonoids from Chinese medicinal herbs have been demonstrated to modulate such pathways, contributing to the regulation of oxidative stress in mice brains [ 72 ].…”
Section: Hibiscus Rooibos Yerba Mate As Sources Of Natural Bioactive ...mentioning
confidence: 99%
“…An overview should be done on related mechanisms in the activation of physiological pathways, such as the SOD (Superoxide dismutase) system, CAT (Catalase), or the downregulation of pro-inflammatory cytokines, such as TNF-α, related to the downstream activation of oxidative stress. Flavonoids from Chinese medicinal herbs have been demonstrated to modulate such pathways, contributing to the regulation of oxidative stress in mice brains [ 72 ].…”
Section: Hibiscus Rooibos Yerba Mate As Sources Of Natural Bioactive ...mentioning
confidence: 99%
“…Sepsis is a common and potentially fatal systemic disorder that generally results in uncontrollable inflammation, tissue damage, and multiple-organ failure. Sepsis and its complications are the leading causes of mortality among intensive care unit patients [ 15 , 16 ]. Excessive inflammation and severe lung epithelial cell apoptosis are regarded as potential mechanisms of sepsis-induced ALI [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Blueberry polyphenols consumption also improved object recognition in rats, which was linked with lower oxidative stress due to the lower NFκB (nuclear factor kappa B) level in different brain areas [29]. Apart from berry juice polyphenols, also tea flavanols were able to improve brain functions in mice with cognitive deficits [34,35]. Animal studies have suggested the utility of plant-derived polyphenolic compounds in amyloid aggregation-related disorders like AD or PD.…”
Section: Impact Of Various Polyphenols On Brain Functions-animal Modelsmentioning
confidence: 99%